Analysis of doctoral theses on tutoring: bibliometric approach and thematic trends - López Gómez, Ernesto (Revista General de Información y Documentación, 2016)
This piece of research analyzes the doctoral theses on tutoring presented at Spanish universities during the period 1980-2014, following the examination of three databases (Teseo, Dialnet, and TDR). After an exhaustive search, a total of 67 doctoral theses were found. The analysis of those theses was conducted considering, on the one hand, bibliometric parameters such as thesis per year, sex, universities, directors, and members of evaluating committees; and, on the other hand, the thematic trends in doctoral research on tutoring, considering descriptors, educational period, and topics. The study concludes with some reflections about the heterogeneity of bibliometric attributes observed in the doctoral thesis on tutoring, as well as a presentation of the thematic trends in the scientific construction of the field tutoring from doctoral theses.
Keywords: Doctoral Thesis; Tutoring; Bibliometry; TESEO database; Spain